The Cycle of Development in Africa: A Story about the Power of Economic Ideas - Martin Paldam (Swiss Journal of Economics and Statistics, 2011)
During the last 60 years development in Sub-Sahara Africa has had three main phases - P1, P2 and P3 - divided by kinks in 1972 and in 1994. P1 and P3 had fairly satisfactory growth, but P2 had negative growth. This cyclical growth path has to be explained by variables with a similar path. A set of socio-economic variables representing 11 hypotheses is considered. Some of these hypotheses have been proposed to explain the low growth of Africa, while most are meant to explain the growth tragedy of P2. Most of the variables have paths with no relation to the cycle, but the path corresponds to the shifts in the dominating development strategy. At the end of P1 the main policy-package in Africa became the one of African socialism. It led to large scale rent seeking, inefficiency and economic regression. At the end of P2 policies were adjustment towards a more market based system and growth resumed.
Keywords: O11; O55; 330; Africa; development policy; institutions